(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The article deals with various definitions of authentic materials. Authentic materials are defined as language samples that are created by native speakers for native speakers of the language. Another similar opinion comes that authentic materials are not for language teaching purposes, but designed texts used for real life use for interactional and transactional purposes. Authentic materials were used for native speaker only, but some teachers used it for teaching purposes. The development of ELT finally places the authentic materials not only for native but also for EFL as their learning media. Authentic materials as printed materials, which are used in classroom in the same way they would be used in real life. For this development of authentic materials use, it is also added that authentic materials in classroom are stretches of real language, produced by real speakers or writers for real audiences and designed to convey real message.